Percepção sobre espécies exóticas e nativas do Brasil por estudantes do ensino médio e superior goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The invasion of exotic species, habitat destruction, and the increase of urbanization generate substantial biodiversity losses and, consequently, keep people apart from native species. In this study, we investigated high-school and undergraduation students’ perceptions on both exotic and native species from Brazil with the application of questionnaires containing questions and a card-board game for the identification of name and origin of different fauna species. Firstly, we evaluated 371 high-school students from two municipalities from the state of Goiás, one with and the other without a conservation unit. We related their knowledge on animal species with their place of residence, their frequency of contact with nature, the frequency of practical classes, and the frequency of visits to the conservation unit. We verified that the students better identified exotic species than Brazilian native species. We also observed that the better identified biological groups were mammals, fishes, and exotic birds. We did not observe students’ perception differences related to their municipality, their residence area, the frequency of contact with nature, practical classes, and visits to the conservation unit. Our results are an evidence that the students’ perceptions were not broad and that they preferred to protect charismatic species, like mammals. In chapter two, we evaluated 509 students from four different graduation courses from environmental sciences (Agronomy, Biological Sciences, Ecology, and Veterinary Sciences) and related their knowledge on different aspects concerning native and exotic species. We observed that the students better identified native species rather than exotic ones. Mammals (exotic and native ones), native birds, and exotic fishes were the taxonomic groups that were better identified. We did not observe perception differences in the four courses we evaluated, comparing students from the begin and end of their courses. Although the majority of the students affirmed they learnt about exotic species during their graduation courses, we verified they do not consider themselves well-informed on the topic. We observed there is an association among the students’ courses/semesters and their knowledge levels. We conclude the students demonstrated their knowledge on native species, but also have knowledge deficits on exotic invasive species. Our study allows a better understanding on highschool and graduation students’ current knowledge level on both exotic and native species and allowed us to propose the elaboration of new teaching strategies and academic curriculum improvements for both high-school and university disciplines.
Perception of exotic and native species from Brazil by high school and college students in the state of Goiás
Keywords: Conservação; Educação ambiental; Biodiversidade; Invasão biológica; Conservation; Environmental education; Biodiversity; Biological invasions; CIENCIAS BIOLOGICAS